An epidemiological study of child marriages in a rural community of Gujarat - Yogita P Pandya; Dinesh J Bhanderi (Wolters Kluwer Medknow Publications, 2015)
Context: India has the maximum number of child marriages (CMs; < 18 years) because of the size of its population, and in 47% of all marriages the bride is a child. Children who are married at young age are exposed to multiple risks pertaining to their physical, mental, and social health. Aims: (i) To estimate the prevalence of CM in rural population. (ii) To study the determinants and health effects of CM. (iii) To assess the awareness among the married women regarding the health implications of CM. Settings and Design: Community-based cross-sectional study conducted in Ardi village of Anand district. Materials and Methods: All the married women of the village were surveyed to find out the prevalence of CM. For collection of other relevant information, only those women having a married life of less than 10years were interviewed using semicoded and pretested questionnaire. Data collected were analyzed using Statistical Package for Social Sciences (SPSS) 17.0 software. Statistical Analysis Used: Proportions, ratios, χ2 test, and Fisher's exact test. Results: The prevalence of CM was found to be 71.5%. Caste and spouse's education were revealed as important determinants for CM. CM was found to be significantly associated with mother's age at birth of first child, delayed antenatal care (ANC), spontaneous abortion, preterm delivery, low birth weight (LBW), health problems in new born baby, faulty feeding practices, lack of knowledge regarding family welfare methods, and health implications of CM. Conclusion: Exceptionally high prevalence of CM in rural community and its serious health consequences warrant stricter enforcement of legislation, better educational opportunities for girls, and easy access to quality health services.